A very brief history of eternity - Eire, Carlos M. N. (Princeton University Press, 2010)
Eire traces the concept of eternity from ancient times to the present. He examines the rise and fall of five different conceptions of eternity, how they developed, and how they have helped shape individual and collective self-understanding.